Mathematical design of the removal process of warts by the ND:YAG-laser - Demkovych, Ihor; Petrovska, Halyna; Oleshkevych, Volodymyr (Видавництво Львівської політехніки, 2012)
Results of the optimization of parameters ND:YAG-laser beaming and conditions of the irradiation are presented for effective warts removal.
Keywords: Wart; Laser; Mathematical design